Investigating the coupling effects of rainfall intensity and slope inclination on soil-rock mixture slope stability and failure modes - Fanyi Zhou; Hengbin Wu; Yue Qiang; Gang Liu; Zhongxu Zhang; Yi Zhang; Nanxi Chen (PLoS ONE, 2025)
The primary factor influencing slope stability is the variation of internal mechanics within the soil-rock mixture caused by rainfall infiltration. Most existing research has focused on how rock content affects the failure of soil-rock mixture slopes. However, there has been insufficient investigation into the coupling effects of rainfall intensity and slope inclination on the stability of soil-rock mixture slopes. Therefore, the model test of soil-rock mixture slope was carried out. The coupling effects of rainfall intensity and slope inclination on water content, earth pressure, pore water pressure, and failure mode of soil-rock mixture slope were analyzed. The failure mode of soil-rock mixture slope induced by rainfall was revealed. The results indicated that an increase in rainfall intensity and slope inclination significantly contributed to the instability of soil-rock mixture slopes and the loss of fine particles. Additionally, the maximum values of water content, earth pressure, and pore water pressure increased progressively. Considering the two influencing factors of rainfall intensity and slope inclination, the calculation formulas related to the fine particle content, maximum water content, maximum earth pressure, and maximum pore water pressure of soil-rock mixture slope were established. The findings of this research provided theoretical support for the construction of soil-rock mixture slopes and the prevention and control of landslide disasters.